Reimagining International Students in Public Discourses: Can Media Facilitate the Inclusion of International Students in Society? - Jokila, Suvi; Plamper, Raakel (n/a, 2026)
The inclusion of international students in campuses and societies is an objective of many countries. While such policies are often accompanied by well-intentioned supportive practices and discourses, these activities may actually produce paradoxes where immigrant groups are excluded as “others” (e.g., Kangas-Müller et al., 2024). Hence, in this paper, by investigating articles published by two primary newspaper outlets from 2010 to 2023, we analyse the media framings and agencies of international students in Finland, a country that is considered a latecomer in both recruiting international students and welcoming immigrants to society. Through these analyses, we identify four main framings to represent international students: as numbers, as labour, as economic resources, and as social others. Three agency categories position international students as predetermined, active, and constrained. We conclude with a discussion of what is not present in Finnish media and the possible implications of public discourses as mediators of inclusive (or exclusive) language and practices.